Relevansi Perkembangan Pemikiran Filosof Muslim Dalam Menjelaskan Antara Filsafat dan Agama Yang Berkesinambungan - Supriani Supriani; Syarifuddin Syarifuddin (Jurnal Budi Pekerti Agama Islam, 2024)
Of all the thoughts of Islamic philosophers, there are still many Muslims who are unable to properly translate their thoughts into people's lives, so that many Muslims lose direction in navigating this life, as a result they move away from Islamic teachings. The aim of this research is to analyze how the thoughts of this Islamic philosopher can be adopted by Muslims in order to carry out Islamic teachings in a sustainable manner. The research method applied is descriptive qualitative with documentation studies, where the data collection technique uses documentation studies. In accordance with the results of existing research, it can be concluded that there are several concepts from Islamic thought that Islamic philosophers have adopted in order to teach Islamic teachings on an ongoing basis, namely the ideas of monotheism, epistemology, metaphysics, ethics, political philosophy, Sufism, Islamic law and theology.